2016
DOI: 10.4132/jptm.2015.07.28
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Disease Presented as a Mural Mass in the Stomach

Abstract: Isolated gastric IgG4-related disease (IgG4-RD) is a very rare tumefactive inflammatory condition, with only a few cases reported to date. A 48-year-old woman was incidentally found to have a subepithelial tumor in the stomach. Given a presumptive diagnosis of gastrointestinal stromal tumor or neuroendocrine tumor, she underwent wedge resection. The lesion was vaguely nodular and mainly involved the submucosa and proper muscle layer. Microscopically, all classical features of type I autoimmune pancreatitis inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 17 publications
(12 reference statements)
2
26
0
3
Order By: Relevance
“…So far, several reports describing cases with gastrointestinal manifestations have been published (Table 1). However, more than half of them did not have extra gastrointestinal manifestations or serum IgG4 elevation, and were diagnosed based only on the pathological examinations [19][20][21]28]. Baez et al reported a case of autoimmune pancreatitis with wall thickening and nodular lesions in the gastric wall [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, several reports describing cases with gastrointestinal manifestations have been published (Table 1). However, more than half of them did not have extra gastrointestinal manifestations or serum IgG4 elevation, and were diagnosed based only on the pathological examinations [19][20][21]28]. Baez et al reported a case of autoimmune pancreatitis with wall thickening and nodular lesions in the gastric wall [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although IgG4-RD mainly involves glandular tissues or the vascular system, several case reports have shown that IgG4-RD also involves the gastrointestinal tract with ulcer, polypoid lesions, submucosal mass, and wall thickening. However, because of the small number of reports on the gastrointestinal lesions of IgG4-RD, their entire spectrum has not yet been adequately documented, and especially, the radiological aspects of many of these lesions are still obscure [19][20][21][22][23][24][25][26][27][28]. Here, we report the detailed imaging findings in a case of IgG4-RD with gastric involvement.…”
Section: Introductionmentioning
confidence: 99%
“…IgG4-RD of the gastrointestinal tract is very rare and can present as diffuse wall thickening or as polyp or mass-like lesion [2,3]. Even though obliterative phlebitis was not present in these two cases, the presence of dense fibrosis, which was storiform in one case, and dense lymphoplasmacytic infiltration with lymphoid aggregates and follicles, presenting as a submucosal masslike lesion, suggested the possibility of IgG4-RD, which was confirmed by IHC and elevated serum IgG4 level.…”
Section: Discussionmentioning
confidence: 66%
“…IgG4-related disease (IgG4-RD) is a newly-recognized, immune-mediated fibroinflammatory disorder that most commonly affects the pancreas [1]. It can also involve other organs such as the bile duct, liver, gallbladder, salivary glands, lacrimal glands, retroperitoneum, and lymph nodes, although involvement of the gastrointestinal tract is very rare [2,3]. The disorder can present as diffuse wall thickening or as polyp or mass-like lesion [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation